Taste Dysfunction in SARS-CoV-2 Infected Patients: A Review of Possible Pathological Mechanisms and Implications - Asmaa Shanab; Dunya Ben Sofia; Ebtesam Aldieb (Khalij-Libya Journal of Dental and Medical Research, 2021)
The coronavirus disease 2019 (COVID-19) is a pandemic infectious disease threatening the world, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). While fever, cough, fatigue and shortness of breath are common symptoms, a sudden chemosensory (taste and/or smell) dysfunctions are increasingly reported in asymptomatic individuals that later test positive for COVID-19. The exact pathogenesis of these chemosensory disorders in SARS-CoV-2 infected patients has not yet been clarified. This review aims to provide a brief review of recent evidence for pathological mechanisms of the taste dysfunction in COVID-19 patients. We also discuss the possibility of using isolated sudden onset of taste alterations as an early symptom of SARS-CoV-2 infection that might be very helpful for reducing the spread of COVID-19 through early identification.